2014
DOI: 10.1038/nm.3585
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic transformation of diverse gastrointestinal tissues in primary organoid culture

Abstract: The application of primary organoid cultures containing epithelial and mesenchymal elements to cancer modeling holds promise for combining the accurate multilineage differentiation and physiology of in vivo systems with the facile in vitro manipulation of transformed cell lines. Here, a single air-liquid interface culture method was used without modification to engineer oncogenic mutations into primary epithelial/mesenchymal organoids from mouse colon, stomach and pancreas. Pancreatic and gastric organoids exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
345
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(363 citation statements)
references
References 42 publications
15
345
0
3
Order By: Relevance
“…Organoids retain the organ structure, morphology, stromal composition, genetic mutations, and heterogeneity of the original tumor (5,(7)(8)(9)(10). When organoids are transplanted into mice, they form carcinomas that resemble the histology of the tumor of origin (5,7,10).…”
Section: Primary Human Organoids As a Model Of Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Organoids retain the organ structure, morphology, stromal composition, genetic mutations, and heterogeneity of the original tumor (5,(7)(8)(9)(10). When organoids are transplanted into mice, they form carcinomas that resemble the histology of the tumor of origin (5,7,10).…”
Section: Primary Human Organoids As a Model Of Cancermentioning
confidence: 99%
“…Organoids are amenable to genetic, biochemical, and imaging assays and have been used to study many aspects of cancer, including carcinogenesis, cancer invasion, drug response, and drug resistance mechanisms. Genetic manipulation of organoids allows study of genetic mutations that drive or suppress cancer progression (7,8,11). Furthermore, studies of organoids have revealed characteristics and mechanisms of tumor-extracellular matrix interactions and cell invasion (12)(13)(14)(15).…”
Section: Primary Human Organoids As a Model Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 30-50 mg of minced tissue was mixed with 400 ”L of ice-cold Matrigel by pipetting using a 2.0 ml pipette and transfer to the cell culture insert. The tissue was allowed to solidify for 10 minutes at 37 o C. The outer dish was subsequently filled to cover the acellular layer with WENRAS media [14,30] [15]. Tumoroid cultures were prepared by washing the tissue fragments 6-8 times in 10 mL of ice-cold PBS allowing the tissue to settle after each wash and removing the supernatant.…”
Section: Establishment Of 3d Air-liquid Interface (Ali) and Tumoroid Cumentioning
confidence: 99%
“…[84][85][86][87] Bmi-1, Notch, Hedgehog, and Wnt, which were initially identified based on their roles in tumor formation, have been shown to be involved in the regulation of self-renewal in normal stem cells in many tissues. [88][89][90] Since myeloma cells are influenced by the host, the microenvironment may play a key role in the initiation of myeloma and associated phenotypic changes-a phenomenon called "plasticity", defined as altered cellular phenotype and function during deregulated differentiation.…”
mentioning
confidence: 99%